Standardy edukacyjne rachunkowości wyznacznikiem nowej jakości kształcenia - Rosiak, Janina; Szczypa, Piotr (Educational Standard of Accountancy as a Premise of New Teaching Quality, 2005)
In the article the authors focus on issues of the implementation of educational standard of accountancy. The empirical example of such a standard of presented. Additionally the authors emphasize the link between using of educational standard of accountancy and quality of teaching students.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 137-141